2015
DOI: 10.1513/annalsats.201501-034oc
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opioids on Breathlessness and Exercise Capacity in Chronic Obstructive Pulmonary Disease. A Systematic Review

Abstract: Opioids improved breathlessness but not exercise capacity in severe COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
181
1
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 189 publications
(193 citation statements)
references
References 37 publications
5
181
1
6
Order By: Relevance
“…A recent prospective observational study of individuals with advanced COPD found that receipt of opioids, among selected patients with careful dose titration and close monitoring for side effects, significantly improved respiratory questionnaire scores and dyspnea ratings at 4-6 months compared with baseline [18]. A more recent systematic review [19] on opioids for refractory dyspnea and exercise intolerance in advanced COPD drew similar conclusions as the earlier one by Jennings et al [16].…”
Section: Editorialsupporting
confidence: 55%
See 4 more Smart Citations
“…A recent prospective observational study of individuals with advanced COPD found that receipt of opioids, among selected patients with careful dose titration and close monitoring for side effects, significantly improved respiratory questionnaire scores and dyspnea ratings at 4-6 months compared with baseline [18]. A more recent systematic review [19] on opioids for refractory dyspnea and exercise intolerance in advanced COPD drew similar conclusions as the earlier one by Jennings et al [16].…”
Section: Editorialsupporting
confidence: 55%
“…First, these trials were all characterized by small numbers of subjects [10,[16][17][18][19] and some studies included individuals without COPD [16,17]. The efficacy and safety of opioids may understandably differ between individuals with COPD versus individuals with lung cancer or congestive heart failure.…”
Section: Editorialmentioning
confidence: 99%
See 3 more Smart Citations